2003
DOI: 10.1149/1.1574032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Atmospheric Corrosion of Copper in the Presence of Ammonium Sulfate Particles

Abstract: The effect of the surface concentration of submicrometer ammonium sulfate (NH 4 ) 2 SO 4 dust particles on the mechanism of atmospheric corrosion of copper has been investigated at 298 K and 93% relative humidity ͑RH͒. For surface concentrations from 1 g/cm 2 to 10 mg/cm 2 , the same corrosion products are formed at relative humidities well above the critical relative humidity of (NH 4 ) 2 SO 4 . Initially, a Cu(NH 3 ) 2ϩ complex is formed. The basic copper sulfate posnjakite precipitates when its solubility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Water from the humid environment can be absorbed onto surfaces covered with fine dust particles containing soluble salts, creating a saturated deliquescence brine layer. [1][2][3][4] Such a layer could be extremely corrosive, even to corrosion-resistant alloys (CRAs) if the temperature were high enough, due to the salt concentration and high availability of oxygen. Furthermore, it is possible that precipitates or rock particulates could act as a crevice former and cause localized corrosion of the substrate metal.…”
mentioning
confidence: 99%
“…Water from the humid environment can be absorbed onto surfaces covered with fine dust particles containing soluble salts, creating a saturated deliquescence brine layer. [1][2][3][4] Such a layer could be extremely corrosive, even to corrosion-resistant alloys (CRAs) if the temperature were high enough, due to the salt concentration and high availability of oxygen. Furthermore, it is possible that precipitates or rock particulates could act as a crevice former and cause localized corrosion of the substrate metal.…”
mentioning
confidence: 99%
“…Lobnig et al reported that the binding energy of S 2p 3/2 for posnjakite is 169?9 eV. 33 For the indoors plate, no basic copper sulphates were found in the XRD pattern, as mentioned above. The peak maximum was very similar to that for CuSO 4 (168?8 eV).…”
Section: Amounts Of Sulphur and Chlorine In Corrosion Productsmentioning
confidence: 82%
“…28 For the outdoors plate (Fig. 2b), posnjakite (934?9 eV) 33 and brochantite (936 eV) 33 were also possible origins in addition to the cupric species. The lower binding energy component originated from cuprite and/or chalcocite because both phases were detected in the XRD patterns for both copper plates.…”
Section: Amounts Of Sulphur and Chlorine In Corrosion Productsmentioning
confidence: 99%
“…At the deliquescence relative humidity (DRH), a sudden phase transition from solid particle to a saturated where only one filter has been sampled. (Chang and Lee, 2002;Ebert et al, 2002;Hu et al, 2010;Möller, 2010;Tang and Munkelwitz, 1994;Wise et al, 2005) NaNO 3 76-80 c -d (Möller, 2010;Tang and Munkelwitz, 1994) Na 2 SO 4 82-83 e 58 (Chang and Lee, 2002;Ebert et al, 2002;Hu et al, 2010;Tang and Munkelwitz, 1994) MgCl 2 33 -(Möller, 2010) NH 4 NO 3 61-62 c b20-30 (Chang and Lee, 2002;Ebert et al, 2002;Frankenthal et al, 1993;Möller, 2010; Sanjurjo-Sánchez and Alves, 2011) (NH 4 ) 2 SO 4 80-81 31-48 (Ciobanu et al, 2010;Ebert et al, 2002;Frankenthal et al, 1993;Hu et al, 2010;Lobnig et al, 2003;Möller, 2010;Wise et al, 2005) NH 4 HSO 4 30-40 - (Frankenthal et al, 1993;Möller, 2010 b5 - (Frankenthal et al, 1993) a The given CRH is valid for PM in the atmosphere. Once deposited on a certain material, the metastable state of the supersaturated droplet can be shifted (Ebert et al, 2002).…”
Section: Composition Of Water-soluble Deposited Mattermentioning
confidence: 99%